Analisa Pengaruh Penggunaan Media Sosial, Motivasi dan Pengetahuan Kewirausahaan terhadap Minat Mahasiswa untuk Berwirausaha - Bambang Satrionugroho; Sri Tomo (Universitas Islam Negeri Sultan Syarif Kasim Riau Pekanbaru, 2020)
The aim of this research is to ananlize the effect of using social media, motivation of entrepreneurship, and knowledge of entrepreneurship to intensity of entrepeneurship of the students of STMIK Sinar Nusantara Surakarta, partially or simultaneously. Research conducted a quantitative study. The population is the STMIK Sinar Nusantara students class in 2017-2019 which has took the Entrepreneurship Study, to 550 with a total sample of 110 students. Methods of data analysis using multiple linear regression analysis technique. The results showedthat the partial and simultaneous of use of social media, motivation and knowledge of entrepreneurship significant effect on student intention in entrepreneurship at the STMIK Sinar Nusantara Surakarta.